Use of virtual reality for treating burned children: case reports - Soliane Quitolina Scapin; Maria Elena Echevarría-Guanilo; Paulo Roberto Boeira Fuculo Junior; Jerusa Celi Martins; Mayara da Ventura Barbosa; Maurício José Lopes Pereima
ABSTRACT Objective: To report the use of virtual reality (VR) in pain intensity during dressing change of two burned children hospitalized in a Burn Treatment Center (BTC) in Southern Brazil. Method: Case report on the use of VR during dressing change of two burned children hospitalized in a BTC, from May to July 2016. For assessing pain, a facial pain rating scale was applied at four times: just before the dressing, during the dressing without the use of VR, during the dressing with the VR, and after the use of VR. Results: The use of goggles was easy to apply and well-accepted by the children, and also had a relevant effect reducing pain. Conclusion: VR can become an important nonpharmacological method for treating pain in burned children.